The relationship between personality and short video addiction among college students is mediated by depression and anxiety - Zhang, Lei; Zhuo, Xing-feng; Xing, Kai; Liu, Yu; Lu, Fang; Zhang, Jia-yi; Qi, Zheng-dong; Zhang, Li; Yu, Zheng-hong; Gu, Chun-rong (Frontiers in Psychology, 2024)
Background Short video addiction (SVA) among college students is influenced by personality traits, namely, neuroticism and agreeableness. However, the role of depression and anxiety as mediators remains unclear. Objective This study aims to explore the mediating role of comorbid depression and anxiety in the relationship between different dimensions of university students’ personalities and SVA. Methods The SPSS PROCESS was utilized to analyze data from 804 university students across seven universities in China. Results The findings show that neuroticism, agreeableness, and extraversion in the personalities of Chinese university students are all significantly linked to SVA; neuroticism and agreeableness in the personalities of university students have a greater impact on SVA; both neuroticism and agreeableness can first induce depression and then lead to anxiety and SVA, whereas only agreeableness can first lead to anxiety and then result in depression and SVA. Conclusion This study uncovers the intricate relationship between personality traits and SVA among college students, emphasizing depression and anxiety as critical chain mediators in this relationship. It reveals that neuroticism and agreeableness significantly influence SVA through specific pathways involving depression and anxiety, indicating that interventions targeting these traits are essential.